Realisasi Citizenship Education Melalui Program Kampus Merdeka - Nanggala, Agil; Suryadi, Karim (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aimed to describe the realization of citizenship education in the learning practice of the Kampus Merdeka program and to analyze the involvement of various parties in the effort to realize citizenship education in the Merdeka Campus program. This study applied a qualitative approach with a literature study method carried out through several activities, namely collecting library data, reading and taking notes, and processing information according to the formulation of the problem discussed. The realization of citizenship education in the learning practice of the Kampus Merdeka program was executed through several activities that directly interact with the community, including research, entrepreneurship, humanitarian projects, independent projects, and thematic Real Work Lectures (KKN) or village building. Efforts to realize citizenship education in the Kampus Merdeka program required several parties, namely the government, academia, the community or society, the private sector, and the media.